2022
DOI: 10.3390/jcm11175223
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Liver Complications in Patients with Diabetes Mellitus—A Review of the Literature

Abstract: The number of diabetes mellitus patients has increased over the last few years in developing countries, along with obesity and sedentary lifestyle. Besides macroangiopathy and microangiopathy, damage to the nerve fibers of the peripheral nervous system is the most common chronic complication of diabetes. Digestive complications in diabetic patients represent a consequence of diabetic autonomic neuropathy involving the gastrointestinal tract, but unfortunately not always evaluated by diabetologists. Aside from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…19 Studies have shown that diabetes result in nonalcoholic steatohepatitis, cirrhosis and hepatic carcinoma. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies have shown that diabetes result in nonalcoholic steatohepatitis, cirrhosis and hepatic carcinoma. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…All of these conditions have been proven to pose a risk for poor outcome of COVID-19 infection [ 17 , 18 ]. MAFLD is often regarded as a hepatic complication of diabetes and, in that sense, may contribute to the development of a more severe form of COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The residual strain was calculated from the morphometric data at no-load and zero stress state as equations [ 1 , 2 ]: Residual Green strain at the mucosal surface: E i =(( C i-n / C i-z )*( C i-n / C i-z )-1)/2 Residual Green strain at the serosal surface: E o =(( C o-n / C o-z )*( C o-n / C o-z )-1)/2 Where C is the circumference and the subscripts i, o, n and z refer to the inner (mucosal) surface, outer (serosal) surface, no-load state and zero-stress state respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Gastrointestinal (GI) disorders is one of the most common diabetic complications [ 1 ]. The main symptoms include abdominal distension, satiety, diarrhea, constipation and fecal incontinence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%